Keanekaragam Jenis Gastropoda Di Hutan Mangrove Jatipapak Resort Kucur Taman Nasional Alas Purwo - Rendy Setiawan; Arif Mohammad Siddiq; Retno Wimbaningrum; Hari Sulistiyowati; Mita Yuni Aditiya (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Research related to the existence and diversity of Gastropod species in the Alas Purwo National Park is still very minimal, especially in mangrove forests. The purpose of this study was to determine the diversity of gastropods in the mangrove forests of Jatipapak Resort Kucur, Alas Purwo National Park. Methods: This study was conducted from April to December 2020. The method used was purposive sampling by following systematic transects of mangrove vegetation. Results: The results of the research obtained were 420 Gastropods belonging to 6 tribes, 11 genera, and 14 species. The diversity of Gastropods in the mangrove forests of Jatipapak TN Alas Purwo is in the moderate category, this is indicated by a value of 1.966 and the similarity of Gastropods is quite evenly distributed with a value of 0.745. Conclusion: Based on these results, the most common species found was Nerita articulata, while the least species found was Ellobium aurisjudae.